PENINGKATAN KEMAMPUAN MEMBACA CEPAT SISWA KELAS VII SMP NEGERI 20 SIGI MELALUI MODEL PEMBELAJARAN EXPLICIT INTRUCTION - Asniar, Asniar; Nur, Yunidar; Harisah, Sitti (BAHASANTODEA, 2017)
The main problem of this research is â€œhow is the application of explicit instruction learning model on fast reading learning at grade VII students of SMP Negeri 20 Sigi?, How to improve studentsâ€™ fast reading skill by applying explicit instruction modelâ€?. The research results show that the application of explicit instruction model in fast reading were done in a phase, namely the orientation phase, percentage, guided training, and self-training. The research results in cycle i which has been done, the average reading speed of students 256.6, unterstanding the content of 57.2 percent with percentage of classical learning mastery was 40,9 percent. Refer to Minimum Achievement Criteria (KKM) which apply in Indonesian languange learning at SMP Negeri 20 Sigi, the average value is 70 and classical learning achievenmt is 80 percent, The results of this research appears to have not reached the standard of mastery. The action of cycle II, studentsâ€™ skill was improved. 22 students have shown the speed of reading of reading of 274.9 speed per minute (KPM) with understanding of the average content of 80.6. Refer to Minimum Achievement Criteria (KKM) which apply in Indonesian languange learning at SMP Negeri 20 Sigi, the result has reached the standar of completeness. Therefore, based on the research results, it can be conclude thet with the application of explicit instruction learning model can improve fast reading skill at grade VII studebts of SMP Negeri 20 Sigi.